IRF4b and IRF8 Negatively Regulate RLR-Mediated NF-κB Signaling by Targeting MITA for Degradation in Teleost Fish - Yan, Xiaolong; Zhao, Xueyan; Zhou, Ming; Sun, Yuena; Xu, Tianjun (Frontiers in Immunology, 2022)
Mediator of IRF3 activation (MITA) is a significant signal adaptor in the retinoic acid-inducible gene-I like receptor (RLR) signaling pathway and plays an important role in the innate immune system. As a transcription factor, nuclear factor kappa B (NF-κB) can be available in many signaling pathways including the RLR signaling pathway and relative to biological processes like immune responses. In this study, it is determined that IRF4b and IRF8 can have a negative effect on NF-κB signaling pathway mediated by MITA in fish. Firstly, it is found that IRF4b and IRF8 have an inhibitory function on MITA-mediated NF-κB signaling pathway. It is interesting that IRF4b and IRF8 have similar functions to achieve precise downregulated and the degradation of MITA through the ubiquitin-proteasome pathway. IRF is taken as the core domain of IRF4b or IRF8 for the downregulation to MITA. This study provides data on MITA-mediated NF-κB signaling pathway in teleost fish and provides new insights into the regulatory mechanism in fish immune system.